Binder-free NiO@MnO2 core-shell electrode: Rod-like NiO core prepared through corrosion by oxalic acid and enhanced pseudocapacitance with sphere-like MnO2 shell. (20th January 2016) - Liu, Xu; Chen, Gang; Guan, Hongtao; Dong, Chengjun; Xiao, Xuechun; Wang, Yude
Graphical abstract: Binder-free NiO@MnO2 core-shell structure applied as electrodes of supercapacitor shows an impressive enhancement of the performance including the areal capacitance and cycling stability. Abstract: Binder-free NiO@MnO2 core-shell structure was deposited on Ni foam used as electrode of supercapacitor. The rod-like NiO core was prepared by thermal decomposition of NiC2 O4 synthesized by corrosion of Ni foam with oxalic acid under hydrothermal conditions. Sphere-like MnO2 shell was deposited on the surface of NiO core through hydrothermal treatment with KMnO4 solution. The structure, composition, morphology evolution and surface chemical state of the NiO@MnO2 electrode were analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray (EDX), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). The obtained NiO and NiO@MnO2 electrodes were directly used as electrodes of supercapacitor, and their electrochemical performances were tested with cyclic voltammograms, galvanostatic charge/discharge and electrochemical impedance spectroscopy. The results show that the sphere-like MnO2 shell leads to an impressive enhancement of the performance including the areal capacitance (AC) and cycling stability, particular in the AC. To be more specific, the NiO@MnO2 exhibits a high AC of 3.584 F/cm 2 at a current density of 5 mA/cm 2, which is much higher than that of NiO electrode whose AC is 1.483 F/cm 2 at the same current density, demonstrating the potential to use NiO@MnO2 electrode for supercapacitor. At the same time, the related mechanisms for the superior performance were also discussed.